2013
DOI: 10.5901/mjss.2013.v4n6p447
|View full text |Cite
|
Sign up to set email alerts
|

Supervision for Quality Assurance in Universal Basic Education Programme in Nigeria

Abstract: This paper discussed quality assurance as the major print out of emphasis towards ensuring standard education in Nigerian educational system. It discussed supervision of instruction as the panacea for quality in the Universal Basic Education in Nigeria Schools. Objectives of UBE and the need for effective supervision of the Scheme were discussed System theory was used as the theoretical frame work in the paper. Strategies for effective supervision were proffered. Recommendations were made among which is provis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…to Glanz and Heinemann (2018). Oluremi and Oyewole (2013) affirm that supervision enhances the teaching and learning process by checking professional records, giving teacher's feedback, and monitoring timetables, leading to good academic performance. Egbai et al (2015) found that school leaders should effectively supervise teachers by ensuring they are observed regularly, prepare lesson plans early, use teaching/learning resources strictly, and adequately implement the curriculum.…”
Section: Pgjsrtmentioning
confidence: 83%
“…to Glanz and Heinemann (2018). Oluremi and Oyewole (2013) affirm that supervision enhances the teaching and learning process by checking professional records, giving teacher's feedback, and monitoring timetables, leading to good academic performance. Egbai et al (2015) found that school leaders should effectively supervise teachers by ensuring they are observed regularly, prepare lesson plans early, use teaching/learning resources strictly, and adequately implement the curriculum.…”
Section: Pgjsrtmentioning
confidence: 83%
“…The result presented in Table 1 indicated that the majority of the secondary school teachers have a positive attitude towards the teaching profession as their response to items 1,2,3,4,5,9,10,12,13,15,16,17,19 and 20 were all positive and above the accepted mean of 2.50. The items 6, 7, 8, 11, 14, and 18 were rejected by the respondents as their mean are all below the accepted mean mark of 2.50.…”
Section: Grand Mean 263 Acceptedmentioning
confidence: 93%
“…According to Oluremi and Oyewole (2013) [13], attitude towards profession implies a person's feelings, behaviour and commitment to the profession or job. Therefore, if a teacher is committed and has positive attitude, then it is sure that his/her performance will be fruitful.…”
Section: Introductionmentioning
confidence: 99%
“…The head teacher needs to provide positive feedback and appropriate resources for the teacher to utilize and understand his duty efficiently. To continue supporting the idea [10] conducted a study in Nigeria on supervision for quality assurance in universal education program in Nigeria and he argued that there is the need of having funds in the schools as the process of supervision and need of having adequate facilities and efficient supervisors. So this means that funds are very important and necessary to the working area especially for head teacher at secondary school.…”
Section: Review Of Related Studiesmentioning
confidence: 99%